Embracing impermanence: life events, fear of COVID-19 and psychological distress in the context of the postepidemic era: a moderated mediation model - Shiyou Fu; Zhengjia Ren; Zihao Yang; Zuoshan Li; Jing Wang; Tianyi Zhao; Xinwei Huang (BMC Psychology)
Abstract Objectives To investigate the relationships between life events and psychological distress in the postepidemic era as well as the effects of fear of COVID-19 (FCV-19) and impermanence on these relationships to enrich the study of the underlying psychological mechanisms of postepidemic psychological distress and to provide a theoretical basis for scientific prevention and intervention in individuals with psychological distress. Methods A survey of 504 adults (71.3% female; age M = 26.87, SD = 10.70) was conducted via the Social Readjustment Rating Scale, the FCV-19 Scale, the Impermanence Scale, the Anxiety Scale and the Depression Scale, and a structural equation model was established to explore the relationships between variables. Results The present study revealed the following: (1) there is a significant positive correlation between life events and psychological distress; (2) FCV-19 completely mediates the relationship between life events and psychological distress; and (3) impermanence moderates the mediation, regulating the path by which life events affect FCV-19 and the path by which FCV-19 affects psychological distress. Conclusions In the postepidemic era, impermanence can effectively mitigate the impact of life events on FCV-19 and the impact of FCV-19 on psychological distress.